Type.Cast: The Heart of Medicine (2017) - Brody School of Medicine (My University, 2017)
An art and literary magazine published by the Brody School of Medicine, Division of Health Sciences. The magazine contains artwork and writings by Brody School of Medicine's medical students and others throughout the Health Sciences Campus.
Keywords: Medicine; Medical Students; art; literature; poetry; artwork